Zadovoljstvo z demokracijo v Sloveniji. Deset let kasneje - Štebe, Janez (Teorija in praksa, 2000)
Winners and losers of transition, be it in political, ideological, economic or social security aspect, differ according to their respective evaluation of democratic regime's reality, of how it works. Here, expectations prior to the velvet revolution are important as well. When explaining satisfaction with democracy, the "1999 Democratisation Survey" offers a basis for analysing the relative strenght of economic and political factors. Results show the importance of actual equipment for free market competition. In addition, satisfaction also depends on political positioning in a sense of support for incumbent government and coalition. Positive experiences with justice of political action might further improve consolidation of democracy in Slovenia.
Keywords: javno mnenje; Slovensko javno mnenje; democracy; demokracija; tranzicija; Slovenia; Slovenija